2015
DOI: 10.1051/sicotj/2015028
|View full text |Cite
|
Sign up to set email alerts
|

Lower reoperation rate for cemented femoral stem than for uncemented femoral stem in primary total hip arthroplasty following a displaced femoral neck fracture

Abstract: Introduction: Acute displaced femoral neck fractures are often treated with cemented hemiarthroplasty (HA). There is increasing evidence that total hip arthroplasty (THA) may be a better alternative, but the degree to which the fixation of the femoral stem used affects the outcome is not fully known. The aim of this study is to compare rates of operative complications and implant survival following THA treatment of displaced femoral neck fractures with either a cemented or an uncemented femoral stem. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…In this cohort, the results were quite compelling, with zero fractures occurring in patients who received either a cemented or collared stem, and all of the postoperative fractures occurring in patients receiving uncemented tapered-wedge or meta-diaphyseal fitting stems. This is consistent with other literature as Chammout et al [37], Andersen et al [38], and Zhang et al [39] reported increased rates of postoperative fractures and reoperation when using uncemented femoral stems compared to cemented in primary THA in the direct lateral, posterior, and all approaches, respectively. Berend and Lombardi [40] cited stem and instrument design as factors that increase fracture rate in patients who undergo primary THA as well.…”
Section: Discussionsupporting
confidence: 91%
“…In this cohort, the results were quite compelling, with zero fractures occurring in patients who received either a cemented or collared stem, and all of the postoperative fractures occurring in patients receiving uncemented tapered-wedge or meta-diaphyseal fitting stems. This is consistent with other literature as Chammout et al [37], Andersen et al [38], and Zhang et al [39] reported increased rates of postoperative fractures and reoperation when using uncemented femoral stems compared to cemented in primary THA in the direct lateral, posterior, and all approaches, respectively. Berend and Lombardi [40] cited stem and instrument design as factors that increase fracture rate in patients who undergo primary THA as well.…”
Section: Discussionsupporting
confidence: 91%
“… 3 , 22 25 Previous studies have shown that 9% to 66% of patients develop acetabular erosion; however, it is observed more frequently at the long-term follow-ups of overweight mobile patients. 22 , 25 34 In a study by Baker et al., 23 acetabular erosion developed in 21 (66%) of 32 patients who underwent HA (mean age, 75 years; range, 63–86 years), and after 36 months of follow-up, a revision surgery (THA) was required for one of these patients. Likewise, Avery et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dislocation is a problem that may require reoperation and reportedly occurs in up to 19% of patients after HA procedures and in up to 22% of patients after THA procedures. 3 , 14 , 16 , 18 20 , 22 , 23 , 25 , 26 , 28 , 30 32 , 34 , 35 , 38 , 39 Baker et al. 23 reported that seven patients with FNFs underwent THA and developed dislocation, and all of them required reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates adjusted for Ochi et al 36 Age, Sex, BMI, Operative side, Follow-up duration, Surgery duration, Preoperative blood loss, Intraoperative complications, dislocations, postoperative complications and reoperations Boukebous et al 37 Age, Gender, CCI Mean value, ADL Mean value, Dementia, Operative time, Transfusion, Stem used, Dislocation, Infection, Femur fracture, Thromboembolism, 1 year survival before adjustment and life threatening complications Kim et al 35 Age, BMI, Male, ASA classification Tabori-Jensen et al 40 Age, Gender, Oxford hip score 31 1 1 1 1 0 4 Homma et al 34 1 1 1 1 0 4 Hwang et al 42 0 0 1 1 0 2 Andersen et al 32 1 1 1 1 0 4 Adam et al 20 1 1 1 1 0 4 Tarasevicius et al 19 1 1 0 1 0 4 Tarasevicius et al 33 1 1 1 1 0 4 Ochi et al 36 1 1 0 1 1 4 Reshed et al 38 1 1 1 1 0 4 Boukebous et al 37 1 1 1 1 1 5 Kim et al 35 1 1 1 1 1 5 Zagorov et al 42 1 1 1 1 0 4 Assi et al 39 1 1 1 1 0 4 Tabori-Jensen et al 41 1 0 1 1 1 4 Tabori-Jensen et al 40 1 1 1 1 0 4…”
Section: Studymentioning
confidence: 99%